2020
DOI: 10.1111/jcal.12499
|View full text |Cite
|
Sign up to set email alerts
|

Powering up flipped learning: An online learning environment with a concept map‐guided problem‐posing strategy

Abstract: Scholars have suggested that flipped learning can be enhanced by designing effective in‐class learning activities to improve students' higher order thinking skills. Problem posing has been recognized as such a learning strategy that has great potential for improving students' higher order thinking skills. However, it has been reported as a challenging task for most students. Research evidence has indicated the potential of engaging students in group learning with step‐by‐step hints when conducting problem‐posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…In this context, Thai et al ( 2017 ) emphasized that FLM is a promising way to increase students' performance. Similarly, Hwang et al ( 2021 ) revealed that the flipped learning model improves students' learning performance by enhancing their higher-order thinking skills. On the other hand, Halili et al ( 2021 ) concluded that FLM enhanced students' motivation to learn, and they had a positive perception towards FLM.…”
Section: Review Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…In this context, Thai et al ( 2017 ) emphasized that FLM is a promising way to increase students' performance. Similarly, Hwang et al ( 2021 ) revealed that the flipped learning model improves students' learning performance by enhancing their higher-order thinking skills. On the other hand, Halili et al ( 2021 ) concluded that FLM enhanced students' motivation to learn, and they had a positive perception towards FLM.…”
Section: Review Literaturementioning
confidence: 94%
“…When the literature is examined, there are investigations of the effectiveness of the FLM in software, mathematics, physics, chemistry, health care, statistics, engineering and many other fields (Behmanesh et al, 2020 ; DeSantis et al, 2015 ; Fernández-Martíne et al, 2020 ; Ghanaat & Habibzadeh, 2021 ; Gannod et al, 2008 ; Huang et al, 2020 ; Jdaitawi, 2020 ; Kettle, 2013 ; Kong, 2015 ; Lestari, 2021 ; Mason et al, 2013 ; McLaughlin et al, 2014 ; Pierce & Fox, 2012 ; Talbert, 2014 ; Touchton, 2015 ; Webb & Doman, 2020 ; Yestrebsky, 2015 ). Moreover, it is seen that studies examining the effects of the FLM on many variables such as academic achievement (Hwang et al, 2021 ; Pierce & Fox, 2012 ), attitude (Chao et al, 2015 ; Güç, 2017 ; Sağlam, 2016 ; Webb & Doman, 2020 ), motivation (Çukurcubaşı, 2016 ; Halili et al, 2021 ), mental risk taking (Çakır & Yaman, 2018 ), and reading level (Cashin, 2016 ) are increasing in the literature. The literature review indicates that the use of the flipped learning model (FLM) in learning environments has increased in recent years.…”
Section: Review Literaturementioning
confidence: 99%
“…Moreover, research further adds that the flipped classroom concept is consistent with active learning, which encourages students to participate in teaching activities instead of passively or blindly listening and learning [56]. In general, the flipped classroom is not a new concept.…”
Section: Flipped Classroom Approachmentioning
confidence: 98%
“…For example, Fatawi et al (2020) indicated that learning online can improve student learning outcomes and engagement through concept maps. Hwang, Chang, et al (2020) indicated that a problem-posing strategy guided by concept maps and adopted in an online learning environment improved the learning performance of students. Compared with students with lower critical thinking, students with a higher level of critical thinking have a more obvious improvement in their learning performance.…”
Section: Introductionmentioning
confidence: 99%